Validitas Lembar Aktivitas Peserta Didik (LAPD) Berbasis Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Berpikir Kritis pada Materi Asam Basa Fase F - Izzy Eka Nur Rochmad; Rusmini (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2026)
This study aimed to develop and validate a Problem Based Learning (PBL)-based Student Worksheet to enhance students’ critical thinking skills on acid-base material in Phase F. This research employed a Research and Development (R&D) approach using Thiagarajan’s 4D development model, consisting of define, design, develop, and disseminate stages. However, this study was limited to the develop stage. The define stage included front-end analysis, learner analysis, task analysis, concept analysis, and learning objectives analysis. The design stage focused on selecting the Student Worksheet as the learning media, determining the format based on Facione’s critical thinking indicators, and designing worksheet components, including cover page, instructions, concept map, reading material links, contextual phenomena, and learning activities. The develop stage involved expert validation by two chemistry lecturers and one chemistry teacher to assess content and construct validity using a Likert scale of 1–5. The Student Worksheet was considered valid if the mode score was categorized as “good” or “very good.” The results showed that the Student Worksheet achieved a “very good” category for content validity, covering material accuracy, relevance of critical thinking skills to learning objectives, alignment of learning outcomes, and linguistic appropriateness. Construct validity, which assessed the suitability of the worksheet with critical thinking indicators, also obtained a “very good” category. Overall, the findings indicated that the developed PBL-based Student Worksheet on acid-base material was valid and feasible for improving students’ critical thinking skills in Phase F and is ready for further classroom implementation.